Testing the Antibacterial Activity of A Serum Preparation of Pegagan Leaf Extract (Centella asiatica (L.) Urban) Against the Bacteria Propionibacterium acnes - Bela Atika Putri; Gigih Kenanga Sari; Mingle A Pistanty (Pratama Medika : Jurnal Kesehatan, 2023)
Centella asiatica (L.) Urban) is one of the wild plants and has various benefits to treat various health problems. Centella asiatica can be used as an antioxidant, antigastritis, antitumor, wound healing, immunomodulator, antiproliferation, antibacterial and so on. Purpose: To know that serum extract of Centella asiatica leaves can provide antibacterial activity of Propionibacterium acnes. Method: The research used is experimental. Centella asiatica (L.) Urban leaves were extracted by maceration with 70% ethanol. Centella asiatica (L.) Urban leaf extract was made into serum with concentrations of 5%, 10% and 15%. Physical stability tests were carried out including organoleptic, homogeneity, pH, spreadability, adhesion and viscosity, then tested for the antibacterial activity of Propionibacterium acnes. Statistical analysis was performed using the ANOVA method. Results: Research shows that gotu kola leaf extract contains chemical compounds including triterpenoids, saponins, flavonoids, alkaloids and tannins. The serum preparation formulation is yellowish green in color, has a distinctive extract odor and is in semisolid form, homogeneous during storage, has a pH, stickiness, spreadability, and viscosity that meet the requirements for a good serum. The results of the drag power research were F1 of 7.68% mm, F2 of 11.52 mm and F3 of 16.68 mm. The statistical test results showed a significant effect on antibacterial activity, namely <0.05.